Greeting of Sándor Balázs, Member of the Hungarian Academy of Science on the occasion of his 80th birthday - Zatykó, F. (International Journal of Horticultural Science, 2006)
Greeting of Sándor Balázs, Member of the Hungarian Academy of Science on the occasion of his 80th birthday